2012
DOI: 10.4103/0974-8490.91033
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and the histopathological study of crude extracts and isolated tecomine from Tecoma stans Bignoniaceae in Iraq

Abstract: Background:Tecoma stans (Bignoniaceae) is a central and south American tree used for the control of diabetes, also known as Yellow Elder, it was collected from the gardens of Al-Jadria in Iraq.Materials and Methods:One of the main reported alkaloidal constituents, tecomine, was isolated and confirmed by spectral analysis. The bacteriological assay for different plant leaves extracts; aqueous, ethanolic, and isolated tecomine were conducted to evaluate the antibacterial effect against gram-negative and gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Costantino et al ( 2003 ) reported that oral intake of flower infusion is beneficial for treatment of diabetes and stomach pains. Tecoma roots are a potential source of anthranilic acid and leaves contain several alkaloids such astamine and tecomine which are known to possess potential hypoglycemic effects (Al-Azzawi et al 2012 ). The root-extracts have also been use in fermentation to make beer.…”
Section: Morphologymentioning
confidence: 99%
“…Costantino et al ( 2003 ) reported that oral intake of flower infusion is beneficial for treatment of diabetes and stomach pains. Tecoma roots are a potential source of anthranilic acid and leaves contain several alkaloids such astamine and tecomine which are known to possess potential hypoglycemic effects (Al-Azzawi et al 2012 ). The root-extracts have also been use in fermentation to make beer.…”
Section: Morphologymentioning
confidence: 99%
“…ex Kunth is an ornamental perennial tropical and subtropical plant belonging to the Bignoniaceae family with green leaves and yellow attractive fragrance flowers and commonly known as yellow trumpetbush or yellow bells [2]. The plant originated in the tropical areas of South America and Mexico and has been cultivated in many countries such as Egypt, Iraq, and the United Arab Emirates UAE [3][4][5]. The presence of different types of secondary metabolites in T. stans, particularly alkaloids, has been reported since 1899, as cited by Jones et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds present in the fruit and flower of Tecoma stans have antioxidant and antiproliferative activity. The chemical compound present in root has anthranilic acid which acts as an antidiabetic agent [4]. The leaves of Tecoma stans inhibit the yeast growth.…”
Section: Introductionmentioning
confidence: 99%